2005
DOI: 10.1007/s11192-005-0027-3
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the core literature on tropical medicine: a bibliometric analysis from 1952-2002

Abstract: The medical specialty of "tropical medicine" only dates back a little more than 100 years and, in the meantime, has gone through several quite distinctive eras. The aim of our study was to investigate trends that occurred in the leading literature on tropical medicine over the past 50 years. We analysed 2,802 original articles published in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 22 publications
(21 reference statements)
0
31
0
Order By: Relevance
“…Although all areas of knowledge have experienced noticeable growth in recent years, diverse studies have drawn attention to the even higher rates reported in scientifi c publications on tropical diseases 11 , particularly leishmaniasis [6][7][8] . Some reasons may include the impulse shown by WHO and the new interest in neglected diseases through initiatives such as the TDR Programme, the Special Programme for Research and Training in Tropical Diseases started in the mid-1970s, the changes in global knowledge, and some outstanding developments and papers that have raised interest in research on the topic 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Although all areas of knowledge have experienced noticeable growth in recent years, diverse studies have drawn attention to the even higher rates reported in scientifi c publications on tropical diseases 11 , particularly leishmaniasis [6][7][8] . Some reasons may include the impulse shown by WHO and the new interest in neglected diseases through initiatives such as the TDR Programme, the Special Programme for Research and Training in Tropical Diseases started in the mid-1970s, the changes in global knowledge, and some outstanding developments and papers that have raised interest in research on the topic 12 .…”
Section: Discussionmentioning
confidence: 99%
“…According to Boreham et al [17], research on Giardia and giardiasis has evolved through three phases: the observational and descriptive approach, the use of quantitative experimental and survey methods, and the use of molecular tools. This study was a purely descriptive analysis of the publications related to Giardia and giardiasis indexed in the PubMed database over four decades, as well as their evolution during this period [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. According to the present study, there has been a steady growth of literature dedicated to Giardia and giardiasis throughout the 40-year period analyzed.…”
Section: Discussionmentioning
confidence: 97%
“…Currently, estimates of global and regional productivity of ongoing research on giardiasis may be of interest. There are international bibliometric studies in tropical medicine and/or parasitic diseases [7][8][9][10][11][12][13][14][15]; however, these have not focused exactly on the field of giardiasis. The purpose of this study was to provide an overview of Giardia and giardiasis research over time, as represented by the quantity of published papers.…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometric analysis is a common research method which has already been widely applied for the scientific production and research trends in many disciplines of science (Keiser and Utzinger, 2005;Van Raan, 2005;Li et al, 2009;Zhang et al, 2013;Liao and Huang, 2014). The Science Citation Index (SCI), from the Institute for Scientific Information (ISI) Web of Science databases is the most frequently used database (Bayer and Folger, 1966;Ho, 2014).…”
Section: Introductionmentioning
confidence: 99%